Effect of a ring on the cyclic conjugation in another ring: applications to acenaphthylene-type polycyclic conjugated molecules - SLAVKO RADENKOVIĆ; SVETLANA JEREMIĆ; IVAN GUTMAN; BORIS FURTULA (Journal of the Serbian Chemical Society, 2010)
In a recent work, a method was developed for assessing the influence ief(G, Z0|Z1) of a ring Z1 on the energy effect of another ring Z0 in a polycyclic conjugated molecule G. Herein, a report is given of detailed numerical investigations of ief(G, Z0|Z1) aimed at the elucidation of the influence of various six-membered rings on the intensity of cyclic conjugation in the five-membered ring of acenaphthylene-type molecules. The earlier discovered regularities for cyclic conjugation in acenaphthylene-type molecules (in particular, the PCP rule and the linear rule) could thus not only be rationalized, but also a number of hitherto concealed regularities could be envisaged.